(untitled) (Global Journal of Human-Social Science, 2024)
This article presents a research study on the representation of aging women on Instagram focusing on the content of four specific influencers The study utilizes content analysis and categorization to understand the themes and subthemes present in the influencers posts The research methodology follows the principles of content analysis and aims to provide both quantitative and qualitative insights into the representation of aging women on the platform The article also presents the use of a coding book to guide the categorization process and ensure the reliability and validity of the study Additionally it highlights the complexity and diversity of experiences related to aging women as well as the challenges and opportunities of conducting research in the online environment The study ultimately aims to contribute to a better understanding of the representations of aging women in digital spaces